Efforts to Combat Sexual Violence Crimes Using the Speak Up Approach in Makassar City - Ruslan Mustari; Siti Zubaidah; Firman Anugrah; Adhe Cristhian (SEAN Institute, 2026)
This study aims to identify and analyze efforts to combat sexual violence using the Speak Up approach and the factors influencing it in Makassar. This study employed an empirical approach, collecting primary and secondary data obtained through literature review and interviews with relevant parties, namely the Makassar City Women's Empowerment and Child Protection Office. The data were then processed descriptively and qualitatively. The results indicate that the Speak Up Program implemented by the Makassar City Women's Empowerment and Child Protection Office is a preemptive effort to combat sexual violence because it focuses on raising awareness, strengthening the initial reporting system, and reducing social barriers for victims so that acts of sexual violence can be prevented or intervened as early as possible. Preventive action is taken by increasing awareness, education, and early reporting to prevent crimes of sexual violence. Repressive action is taken by encouraging victims and the community to report cases immediately so that cases can be followed up by law enforcement. The implementation of the Speak Up Program is significantly impacted by several inhibiting factors, including negative stigma against victims, lack of access to information, limited resources, pressure from external parties, and the impartiality of law enforcement officials.